Nose-to-brain siRNA delivery by PEI/PPI-based nanoparticles reduces α-synuclein expression in a Parkinson’s disease mouse model - Feja, Malte; Drath, Isabell; Weiß, Sandra; Ewe, Alexander; Gericke, Birthe; Outeiro, Tiago F.; Stefanis, Leonidas; Aigner, Achim; Richter, Franziska (Molecular therapy. Nucleic acids, 2025)
Potential strategies to develop new treatments for Parkinson’s disease (PD) aim at targeting disease-associated proteins like alpha-synuclein (aSyn), which accumulates in neurons of PD patients and contributes to neuronal degeneration. A promising new approach is the therapeutic use of small interfering RNAs (siRNAs) for aSyn knockdown, but is challenging due to siRNA instability, poor delivery, and inefficient uptake. Therefore, we developed a nanoparticle-based approach for intranasal delivery of siRNAs, circumventing the blood-brain barrier and enhancing the potential of siRNAs for clinical application. Tyrosine-modified polyethylenimines (PEIs), or polypropylenimine dendrimers (PPIs), were complexed with siRNA targeting the aSyn-encoding gene SNCA (siSNCA) and combined with liposomes. Nanoparticles efficiently transfected SH-SY5Y cells with low cytotoxicity and significantly reduced SNCA mRNA levels. In Thy1-aSyn mice, intranasally administered labeled nanoparticles distributed extensively across the brain, including the olfactory bulb, substantia nigra, and prefrontal cortex. After only 4 days of treatment, siSNCA-loaded nanoparticles significantly reduced aSyn protein and SNCA mRNA levels in the brain. Mice showed neither overt adverse behavioral effects nor increased reactive microglia. These findings highlight the potential of nanoparticle-mediated intranasal siRNA delivery as a promising, non-invasive approach to reduce aSyn levels in the brain, offering a novel therapeutic strategy for Parkinson’s disease. [Display omitted] Intranasal nanoparticle delivery of siRNA effectively reduces brain alpha-synuclein levels in a Parkinson’s disease mouse model, offering a non-invasive therapeutic strategy with clinical potential.